Carbon-free refractory material and preparation method thereof
Through the raw material composition and preparation method of carbon-free refractory materials, the problem of performance degradation of carbon-containing refractory materials when reducing carbon content is solved, and the application of refractory materials with low carbon emissions, long life and high efficiency and energy-saving are achieved.
Patent Information
- Application Number
- CN202510776995.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-29
AI Technical Summary
While reducing the carbon content, existing carbon-containing refractory materials have problems such as corrosion resistance and thermal shock stability, increasing carbon steel, high production energy consumption and large CO2 emissions.
The raw material composition and preparation method of carbon-free refractory materials are adopted, including high-purity electromelted magnesium sand particles, pre-synthetic magnesium-aluminum spinel fine powder, nanozirconia, magnesium phosphate colloids, etc., through isostatic molding and two-stage sintering, a carbon-free bonding network is formed to improve material performance.
The carbon content is less than 0.3%, reducing CO2 emissions by 15-20%, extending the service life of the furnace lining by 20-30%, reducing production energy consumption by 15-20%, and reducing thermal conductivity by 50%. It is suitable for high-temperature containers such as converters and RH refining furnaces.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a refractory material and a preparation method thereof, in particular to a carbon-free refractory material and a preparation method thereof. Background Art
[0002] Refractory materials are the basic materials for high-temperature industries such as steel, nonferrous metals, and electricity. They can withstand extreme high temperatures and protect the safe operation of industrial kilns and high-temperature equipment. They play a vital role in the high-temperature industrial field.
[0003] Magnesia-carbon refractories are carbon-containing, unburned products made primarily of magnesium oxide and graphite, with resins and other materials serving as binders. They are primarily used in converters, electric arc furnaces, and ladles. This is due to their poor wettability with molten slag and their excellent thermal conductivity, which can improve the corrosion resistance and thermal shock stability of furnace linings, significantly extending their service life. Therefore, they are widely used in industries such as steel and metallurgy. However, due to their carbon content exceeding 10%, these traditional magnesia-carbon refractories are susceptible to oxidation, which can lead to the formation of pores in the refractory, reducing its corrosion resistance and shortening its service life. Furthermore, carbon readily dissolves in molten steel, causing carbonization and hindering the production of low-carbon and ultra-low-carbon steels. Furthermore, the high thermal conductivity of magnesia-carbon refractories increases energy consumption. Furthermore, their production requires significant amounts of graphite resources, and CO2 emissions also increase with the use of carbon-containing refractories.
[0004] With my country's increasing emphasis on environmental protection and the proposed dual carbon goals, high-temperature industries such as steel and metallurgy are increasingly demanding energy conservation, consumption reduction, and carbon emission reduction. Lowering the carbon content in carbon-containing refractories can reduce their carbon addition to molten steel, reduce CO2 emissions, and conserve mineral resources. Consequently, the refractory industry is developing research on carbon-containing refractories in a low-carbon direction. However, as the carbon content decreases, the particles fail to form a continuous phase, affecting the erosion resistance and thermal shock stability of carbon-containing refractories. Therefore, resolving this contradiction—reducing the carbon content of carbon-containing refractories while maintaining their performance—has become a critical issue that the industry urgently needs to address.
[0005] After searching: Chinese patent application number CN202210389495.6 discloses a method for improving the performance of low-carbon magnesium-carbon bricks. The method involves adding composite fine powder to a low-carbon magnesium-carbon brick matrix material with a carbon content of 2-6 wt%, and adding 8-15% boron / copper oxide to a liquid resin binder. This method uses a copper-containing composite catalytic in-situ formation of a SiC / SiO2 micro-nanofiber network to enhance performance. However, the carbon content in this document is still relatively high, and the use of resin as a binder poses environmental risks and can easily lead to carbon enrichment of molten steel.
[0006] Chinese patent application number CN201610055912.8 discloses a method for preparing low-carbon magnesium-carbon bricks. The raw materials used are: 90-95 parts magnesia; 3-8 parts micronized graphite; 1-2 parts aluminum powder; 2-4 parts magnesium-aluminum binder; and 1-2 parts water. The method eliminates the use of phenolic resin, resulting in minimal environmental pollution and ideal strength and density at both room and high temperatures. However, the carbon content in the examples in this document is still greater than 5%, and compressive strength and other indicators are comparable to those of conventional carbon-containing refractories, demonstrating no advantages. Summary of the Invention
[0007] The present invention aims to overcome the shortcomings of the existing technology and provide a carbon-free refractory material. Compared with traditional carbon-containing refractory materials, the carbon content of the refractory material does not exceed 0.3%, carbon increase of molten steel can be avoided, CO2 emissions can be reduced by about 15-20% during the production process, the generation of CO, CO2 and benzene series substances can be avoided during use, carbon emissions are reduced, the high-temperature strength of the material can be improved, the structural stability of the furnace lining is further improved, the thermal shock stability and corrosion resistance of the refractory material are improved, the service life of the furnace lining is extended by 20-30%, production energy consumption is reduced by 15-20%, the thermal conductivity is 50% lower than that of the carbon-containing refractory material, and the heat loss of the furnace body is reduced to 30-50%. The present invention also provides a preparation method.
[0008] Measures to achieve the above objectives: A carbon-free refractory material comprises the following raw material compositions and contents by mass percentage: 55-65% of high-purity fused magnesia particles with a particle size of 5 mm or less, 5-10% of high-purity fused magnesia fine powder with a particle size of 0.088 mm or less, 15-25% of pre-synthesized magnesia alumina spinel fine powder with a particle size of 200 nm or less, 4-6% of zirconium oxide with a particle size of 100 nm or less, 3-5% of magnesium phosphate colloid with a particle size of 30 nm or less, 1-3% of stabilized zirconium oxide fibers with a diameter of 1-5 μm, 0.5-1.0% of lithium silicate with a particle size of 3 μm or less, 0.5-1.0% of rare earth oxide with a particle size of 100 nm or less, 0.1-0.5% of titanium boride with a particle size of 50 nm or less, and 0.2-0.5% of ammonium polyacrylate with a particle size of 10 μm or less.
[0009] The invention is characterized in that the mass percentage content of MgO in the high-purity fused magnesia particles with a particle size of ≤5 mm and a particle size of ≤0.088 mm is not less than 98%.
[0010] The invention is characterized in that: the pre-synthesized magnesium-aluminum spinel fine powder with a particle size of ≤200nm is a spinel fine powder synthesized by a co-precipitation method; and the mass percentage of MgO+Al2O3 in the pre-synthesized magnesium-aluminum spinel fine powder is not less than 99%.
[0011] The invention is characterized in that: the stable zirconium oxide accounts for 99% of the zirconium oxide with a particle size of ≤100nm; and the stable zirconium oxide is a ZrO2 ceramic with a dual-phase structure consisting of a cubic phase and a tetragonal phase.
[0012] The invention is characterized in that: the mass percentage of ZrO2+Y2O3 in the zirconia fiber with a diameter of 1 to 5 μm is not less than 99.5%; and the fiber is a completely cubic phase.
[0013] The invention is characterized in that: the mass percentage content of Mg3(PO4)2 in the magnesium phosphate colloid with a particle size of ≤30nm is not less than 40%, and the pH value is between 6.5 and 7.
[0014] The invention is characterized in that: the mass percentage content of Li2SiO3 in the lithium silicate is not less than 99%.
[0015] The invention is characterized in that: the rare earth oxide is a mixture of one or more of lanthanum oxide, yttrium oxide and ytterbium oxide; and the mass percentage content of impurities in the rare earth oxide is controlled to be ≤0.1%.
[0016] The invention is characterized in that: the mass percentage content of NH4PAA in the ammonium polyacrylate is ≥95%.
[0017] A method for preparing a carbon-free refractory material, comprising the following steps: 1) Pre-treating the following raw materials: ultrasonically dispersing 4-6% zirconium oxide with a particle size of ≤100 nm, 0.5-1.0% rare earth oxide with a particle size of ≤100 nm, and 0.5-1.0% titanium boride with a particle size of ≤50 nm; heat treating the zirconium oxide fiber at 490-510° C. for 55-65 minutes to remove surface organic matter; 2) Dry mixing: 55-65% of high-purity fused magnesia particles with a particle size of ≤5 mm, 5-10% of high-purity fused magnesia fine powder with a particle size of ≤0.088 mm, 15-25% of pre-synthesized magnesia alumina spinel fine powder with a particle size of ≤200 nm, and 0.2-0.5% of ammonium polyacrylate with a particle size of ≤10 μm are mixed uniformly with the powders pretreated in step 1); 3) Wet mixing: Add magnesium phosphate colloid with a particle size of ≤30 nm to the dry mix obtained in step 2) in three portions and stir until uniform. The amount of magnesium phosphate colloid with a particle size of ≤30 nm to be added in three portions is as follows: 45-55% of the total amount is added in the first portion, 25-35% of the total amount is added in the second portion, and the remaining amount is added in the third portion. 4) Final mixing: Add 1-3% of zirconia fiber with a particle size of 1-5 μm and 0.5-1.0% of lithium silicate with a particle size of ≤3 μm to the wet mixture in step 3) and stir until uniform; Note: In steps 1) to 4) above, the ambient humidity should be controlled to be ≤40% and the ambient temperature to be ≤35°C. 5) Use isostatic pressing, and control the pressure to not less than 195 MPa, and the holding time to not less than 28 minutes; 6) Drying: Control the drying temperature to be no less than 100°C and the drying time to be 22 to 25 hours; 7) Sintering: adopt two-stage sintering, that is, the sintering temperature in the first stage is controlled to be not less than 800℃ and kept at this temperature for at least 1.5 hours; the sintering temperature in the second stage is controlled to be not less than 1600℃ at a heating rate of ≤3℃ / min and kept at this temperature for at least 5.5 hours; 8) Allow to cool naturally to room temperature and set aside.
[0018] The role and mechanism of each raw material and main process in the present invention The reason for adding high-purity fused magnesia particles with a particle size of ≤5 mm and controlling the content to 55-65% is that the high-purity fused magnesia particles act as a framework in the refractory material of the present invention, providing high-temperature stability and corrosion resistance. Exceeding the content range will affect the material's performance.
[0019] The reason for adding high-purity fused magnesia fine powder with a particle size of ≤0.088mm and controlling the content to 5-10% is that the high-purity fused magnesia fine powder acts as a filler in the present invention, ensuring a reasonable particle size distribution of the raw materials. After mixing, it easily forms a dense packing, increasing the material density and thus improving its strength and corrosion resistance. A content exceeding this range will affect the material properties.
[0020] The present invention adds pre-synthesized magnesium-aluminum spinel fine powder with a particle size of ≤200nm and controls the content to 15-25% because it reduces the thermal expansion effect of the in-situ generated spinel in the material, improving thermal shock resistance. Exceeding this content can affect material performance.
[0021] The reason why the present invention adds rare earth oxides with a particle size of ≤100nm and controls the content to 0.5-1.0% is that rare earth oxides can improve the sintering performance of the material, promote grain boundary strengthening, optimize grain boundary structure, and inhibit abnormal growth of grains at high temperatures.
[0022] The reason why the present invention adds zirconia with a particle size of ≤100nm, 4-6%, and controls the content is because nano zirconia is partially stabilized zirconia, and utilizes the phase transformation toughening mechanism to improve the fracture toughness of the material.
[0023] The reason why the present invention adds magnesium phosphate colloid with a particle size of ≤30nm and controls the content to 3-5% is that the magnesium phosphate colloid acts as a binder in the refractory material of the present invention, replacing the traditional resin binder, forming a carbon-free bonding network through the sol-gel process, and generating a magnesium phosphate reinforcement phase at high temperature.
[0024] The reason why the present invention adds zirconia fibers with a particle size of 1 to 5 μm and controls the content to be 1 to 3% is that the zirconia fibers serve as non-carbon fiber reinforcement phases to improve the thermal shock stability and mechanical impact resistance of the refractory material.
[0025] The reason why the present invention adds lithium silicate with a particle size of ≤3μm and controls the content to 0.5-1.0% is that lithium silicate plays a low-temperature sintering role in the refractory material of the present invention, reduces the sintering temperature of the material and promotes the interface bonding between spinel and magnesia.
[0026] The reason why the present invention adds titanium boride with a particle size of ≤50nm and controls the content to be 0.5-1.0% is that nano titanium boride plays a high-temperature antioxidant role in the refractory material of the present invention and generates a TiO2-B2O3 composite protective layer in an oxidizing atmosphere.
[0027] The reason why the present invention adds ammonium polyacrylate with a particle size of ≤10 μm and controls the content to be 0.2-0.5% is that the ammonium polyacrylate plays a dispersing role in the refractory material of the present invention and inhibits the agglomeration of nano powders.
[0028] The present invention ultrasonically disperses 4-6% of zirconium oxide with a particle size of ≤100 nm, 0.5-1.0% of rare earth oxide with a particle size of ≤100 nm, and 0.5-1.0% of titanium boride with a particle size of ≤50 nm; and heat-treats the zirconium oxide fiber at 500° C. for 1 hour. This is because the raw materials are pretreated and ultrasonic dispersion is performed to facilitate dry mixing and ensure that the raw materials are evenly mixed in subsequent steps. The heat treatment of the zirconium oxide fiber is to remove surface organic matter.
[0029] The reason why the present invention uniformly mixes the powders pretreated in step 1) with 55-65% of high-purity fused magnesia particles with a particle size of ≤5 mm, 5-10% of high-purity fused magnesia fine powder with a particle size of ≤0.088 mm, 15-25% of pre-synthesized magnesia alumina spinel fine powder with a particle size of ≤200 nm, and 0.2-0.5% of ammonium polyacrylate with a particle size of ≤10 μm is that dry mixing provides a basis for subsequent wet mixing, ensuring that the components of various parts of the material are the same and the performance is consistent after molding.
[0030] The reason why the magnesium phosphate colloid with a particle size of ≤30 nm is added to the dry mix after dry mixing in step 2) in three times and stirred until uniform; the distribution of the amount of magnesium phosphate colloid with a particle size of ≤30 nm added in three times is as follows: 45-55% of the total amount is added in the first addition, 25-35% of the total amount is added in the second addition, and the remaining amount is added in the third addition. This is because wet mixing is to fully mix the binder magnesium phosphate colloid with the raw materials to ensure the strength of the material after molding.
[0031] The reason why the present invention adds 1-3% of zirconia fibers with a particle size of 1-5 μm and 0.5-1.0% of lithium silicate with a particle size of ≤3 μm to the wet mixture in step 3) and stirs until uniform is that the mixing step adopts gradient mixing, which is compatible with the mixing requirements of micron-sized particles and nanopowders, solves the problems of raw material agglomeration, stratification, and segregation, and ensures that the components of each part of the material are the same and the performance is consistent after molding.
[0032] The reason why the present invention adopts isostatic pressing and controls the pressure to be not less than 195 MPa and the holding time to be not less than 28 minutes is that isostatic pressing can ensure that the material density is ≥95%.
[0033] The reason why the present invention controls the drying temperature to be not less than 100° C. and the drying time to be 22 to 25 hours is that drying can remove moisture in the green body and improve the strength of the green body.
[0034] The present invention adopts two-stage sintering, that is, in the first stage, the sintering temperature is controlled to be not less than 800°C and kept at this temperature for at least 1.5 hours; in the second stage, the sintering temperature is controlled to be not less than 1600°C at a heating rate of ≤3°C / min and kept at this temperature for at least 5.5 hours. This is because the volatile matter of the binder and the like can be eliminated in the pre-burning stage, and the densification and bonding of magnesia and spinel are promoted in the sintering stage.
[0035] Compared with existing technologies, this invention eliminates carbon-containing raw materials such as graphite and resin. Magnesium phosphate is used as a binder, minimizing the carbon content to less than 0.2% (almost negligible), thus avoiding the problem of carbon enrichment in molten steel. Furthermore, it reduces CO2 emissions by approximately 15-20% during production and avoids the generation of CO, CO2, and benzene-related substances during use, making it environmentally friendly and reducing carbon emissions in steel mills. Phase transformation toughening of zirconia and grain boundary strengthening by rare earth oxides enhances the material's high-temperature strength, improves the structural stability of the furnace lining, and reduces the risk of spalling. Toughening with presynthesized spinel and zirconia fibers buffers thermal stress, improves the material's thermal shock resistance, adapts to frequent temperature fluctuations, and reduces unplanned furnace shutdowns. Densification with fine powders of zirconia (≤100nm) and presynthesized magnesia-alumina spinel enhances corrosion resistance, extending the life of the furnace lining by 20-30% and reducing the need for reconditioning. The use of lithium silicate as a sintering aid allows the sintering temperature to be approximately 100°C lower than that of traditional refractory materials, reducing production energy consumption by 15-20%. The material's low-thermal-conductivity nanostructure and fiber insulation offer a thermal conductivity 50% lower than carbon-containing refractory materials, reducing furnace heat loss by 30-50%. For a 200-ton converter, for example, this reduces heat loss by 0.5-0.8 GJ per heat, equivalent to saving 14-22 kg of standard coal per furnace, resulting in significant energy savings. It can also be used in carbon-sensitive high-temperature vessels such as converters, RH refining furnaces, and tundishes, meeting the demands of smelting high-value-added steel grades. DETAILED DESCRIPTION
[0036] The present invention is described in detail below: Table 1 is a list of raw material values for various embodiments and comparative examples of the present invention; Table 2 is a list of main process parameters of various embodiments and comparative examples of the present invention; Table 3 is a table of performance test results of various embodiments of the present invention and comparative examples.
[0037] Each embodiment of the present invention is produced according to the following steps 1) Pre-treating the following raw materials: ultrasonically dispersing 4-6% zirconium oxide with a particle size of ≤100 nm, 0.5-1.0% rare earth oxide with a particle size of ≤100 nm, and 0.5-1.0% titanium boride with a particle size of ≤50 nm; heat treating the zirconium oxide fiber at 490-510° C. for 55-65 minutes to remove surface organic matter; 2) Dry mixing: 55-65% of high-purity fused magnesia particles with a particle size of ≤5 mm, 5-10% of high-purity fused magnesia fine powder with a particle size of ≤0.088 mm, 15-25% of pre-synthesized magnesia alumina spinel fine powder with a particle size of ≤200 nm, and 0.2-0.5% of ammonium polyacrylate with a particle size of ≤10 μm are mixed uniformly with the powders pretreated in step 1); 3) Wet mixing: Add magnesium phosphate colloid with a particle size of ≤30 nm to the dry mix obtained in step 2) in three portions and stir until uniform. The amount of magnesium phosphate colloid with a particle size of ≤30 nm to be added in three portions is as follows: 45-55% of the total amount is added in the first portion, 25-35% of the total amount is added in the second portion, and the remaining amount is added in the third portion. 4) Final mixing: Add 1-3% of zirconia fiber with a particle size of 1-5 μm and 0.5-1.0% of lithium silicate with a particle size of ≤3 μm to the wet mixture in step 3) and stir until uniform; Note: In the above steps 1) to 4), the ambient humidity should be controlled to ≤40% and the ambient temperature to ≤35℃. 5) Use isostatic pressing, and control the pressure to not less than 195 MPa, and the holding time to not less than 28 minutes; 6) Drying: Control the drying temperature to be no less than 100°C and the drying time to be 22 to 25 hours; 7) Sintering: adopt two-stage sintering, that is, the sintering temperature in the first stage is controlled to be not less than 800℃ and kept at this temperature for at least 1.5 hours; the sintering temperature in the second stage is controlled to be not less than 1600℃ at a heating rate of ≤3℃ / min and kept at this temperature for at least 5.5 hours; 8) Allow to cool naturally to room temperature and set aside.
[0038] Table 1 List of raw material values for various embodiments and comparative examples of the present invention (wt%)
[0039] Note: The examples in Table 1 above: The particle size of high-purity fused magnesia is ≤5mm, and its MgO mass percentage content is not less than 98%; the particle size of high-purity fused magnesia fine powder is ≤0.088mm, and its MgO mass percentage content is not less than 98%; the particle size of pre-synthesized magnesia alumina spinel fine powder is ≤200nm, and its MgO+Al2O3 mass percentage is not less than 99%; the particle size of zirconium oxide is ≤100nm, and its mass percentage content of partially stabilized zirconium oxide is not less than 99%; the particle size of magnesium phosphate colloid is ≤30nm, and its mass percentage content of Mg3(PO4)2 is not less than 40 %, pH values are all within the range of 6.5-7; the diameters of the zirconia fibers are all within the range of 1-5μm, and the mass percentage of ZrO2+Y2O3 contained therein is ≥99.5%; the particle size of the lithium silicate is all ≤3μm, and the mass percentage of Li2SiO3 contained therein is not less than 99%; the particle size of the rare earth oxide is all ≤100nm, and the mass percentage of rare earth oxide contained therein is not less than 99.9%; the particle size of the titanium boride is all ≤50nm, and the mass percentage of TiB2 contained therein is not less than 99%; the particle size of the ammonium polyacrylate is all ≤10μm, and the mass percentage of NH4PAA contained therein is ≥95%.
[0040] Table 2 List of main process parameter values of various embodiments of the present invention and comparative examples
[0041] Table 3 Performance test results of various embodiments of the present invention and comparative examples
[0042] Note: In Table 3: The data of slag erosion depth / width are obtained by static crucible method at 1600℃; The data for thermal conductivity W / m•K were obtained at 1000°C; The data of thermal shock cycle number were obtained under water cooling at 1100℃.
[0043] As can be seen from Table 3, Comparative Example 1 adopts the formulation of traditional low-carbon magnesium-carbon refractory materials, adds graphite powder, and replaces magnesium phosphate colloid with phenolic resin, so that the carbon content is much higher than that of the embodiment, the thermal conductivity is also increased, and the energy consumption is increased.
[0044] Comparative Example 2 uses graphite powder instead of zirconium oxide and zirconium oxide fiber. The carbon content is also much higher than that of the embodiment. The slag erosion resistance is reduced, the thermal conductivity is increased, and the thermal shock stability is reduced.
[0045] This specific implementation is only the best example and is not a restrictive implementation of the technical solution of the present invention.
Claims
1. A carbon-free refractory material, comprising the following raw material compositions and contents by mass percentage: 55-65% of high-purity fused magnesia particles with a particle size of 5 mm or less, 5-10% of high-purity fused magnesia fine powder with a particle size of 0.088 mm or less, 15-25% of pre-synthesized magnesia alumina spinel fine powder with a particle size of 200 nm or less, 4-6% of zirconium oxide with a particle size of 100 nm or less, 3-5% of magnesium phosphate colloid with a particle size of 30 nm or less, 1-3% of stabilized zirconium oxide fibers with a diameter of 1-5 μm, 0.5-1.0% of lithium silicate with a particle size of 3 μm or less, 0.5-1.0% of rare earth oxide with a particle size of 100 nm or less, 0.1-0.5% of titanium boride with a particle size of 50 nm or less, and 0.2-0.5% of ammonium polyacrylate with a particle size of 10 μm or less.
2. A carbon-free refractory material according to claim 1, characterized in that: The mass percentage content of MgO in the high-purity fused magnesia particles with a particle size of ≤5 mm and a particle size of ≤0.088 mm is not less than 98%.
3. The carbon-free refractory material according to claim 1, wherein: The pre-synthesized magnesium-aluminum spinel fine powder with a particle size of ≤200 nm is a spinel fine powder synthesized by a co-precipitation method; and the mass percentage of MgO+Al2O3 in the pre-synthesized magnesium-aluminum spinel fine powder is not less than 99%.
4. The carbon-free refractory material according to claim 1, wherein: The stable zirconium oxide accounts for 99% of the zirconium oxide with a particle size of ≤100 nm; the stable zirconium oxide is a ZrO2 ceramic with a dual-phase structure consisting of a cubic phase and a tetragonal phase.
5. The carbon-free refractory material according to claim 1, characterized in that: The stabilized zirconia fiber with a diameter of 1 to 5 μm contains ZrO2+Y2O3 in a mass percentage of not less than 99.5%; the stabilized zirconia fiber is added with rare earth elements and is a completely cubic phase.
6. The carbon-free refractory material according to claim 1, wherein: The mass percentage content of Mg3(PO4)2 in the magnesium phosphate colloid with a particle size of ≤30nm is not less than 40%, and the pH value is between 6.5 and 7.
7. The carbon-free refractory material according to claim 1, characterized in that: The mass percentage content of Li2SiO3 in the lithium silicate is not less than 99%.
8. The carbon-free refractory material according to claim 1, wherein: The rare earth oxide is a mixture of one or more of lanthanum oxide, yttrium oxide, and ytterbium oxide; the mass percentage content of impurities in the rare earth oxide is controlled to be ≤0.1%.
9. The carbon-free refractory material according to claim 1, wherein: The mass percentage content of NH4PAA in the ammonium polyacrylate is ≥95%.
10. A method for preparing a carbon-free refractory material according to claim 1, comprising the steps of: 1) Pre-treat the following raw materials: 4-6% zirconium oxide with a particle size of ≤100nm, 0.5-1.0% rare earth oxide with a particle size of ≤100nm, and titanium boride with a particle size of ≤50nm: 0.5-1.0% were ultrasonically dispersed respectively; the zirconia fiber was heat treated at 490-510℃ for 55-65min to remove surface organic matter; 2) Dry mixing: 55-65% of high-purity fused magnesia particles with a particle size of ≤5 mm, 5-10% of high-purity fused magnesia fine powder with a particle size of ≤0.088 mm, 15-25% of pre-synthesized magnesia alumina spinel fine powder with a particle size of ≤200 nm, and 0.2-0.5% of ammonium polyacrylate with a particle size of ≤10 μm are mixed uniformly with the powders pretreated in step 1); 3) Wet mixing: Add magnesium phosphate colloid with a particle size of ≤30 nm to the dry mix obtained in step 2) in three portions and stir until uniform. The amount of magnesium phosphate colloid with a particle size of ≤30 nm to be added in three portions is as follows: 45-55% of the total amount is added in the first portion, 25-35% of the total amount is added in the second portion, and the remaining amount is added in the third portion. 4) Final mixing: Add 1-3% of zirconia fiber with a particle size of 1-5 μm and 0.5-1.0% of lithium silicate with a particle size of ≤3 μm to the wet mixture in step 3) and stir until uniform; Note: In steps 1) to 4) above, the ambient humidity should be controlled to be ≤40% and the ambient temperature to be ≤35°C. 5) Use isostatic pressing, and control the pressure to not less than 195 MPa, and the holding time to not less than 28 minutes; 6) Drying: Control the drying temperature to be no less than 100°C and the drying time to be 22 to 25 hours; 7) Sintering: adopt two-stage sintering, that is, the sintering temperature in the first stage is controlled to be not less than 800℃ and kept at this temperature for at least 1.5 hours; the sintering temperature in the second stage is controlled to be not less than 1600℃ at a heating rate of ≤3℃ / min and kept at this temperature for at least 5.5 hours; 8) Allow to cool naturally to room temperature and set aside.
Citation Information
Patent Citations
Preparation method of low-carbon magnesia carbon brick
CN105712705A
A method for improving the performance of low-carbon magnesia-carbon bricks
CN114620997B